A glossy mutant in onion (Allium cepa L.) shows decreased expression of wax biosynthesis genes - Manape, Tushar Kashinath; Soumia, Parakkattu S.; Khade, Yogesh P.; Satheesh, Viswanathan; Anandhan, Sivalingam (Frontiers in Plant Science, 2023)
Cuticular wax is a characteristic feature of land plants that provides protection against both biotic and abiotic stresses. In this study, a glossy mutant lacking an epicuticular wax layer was identified in the γ-irradiated M2 mutant population of the onion cultivar Bhima Super. The inheritance of the mutant’s glossy phenotype was determined to be recessive and single locus. Scanning electron microscopy analysis showed poor accumulation of wax crystals in the glossy mutant, concentrated near the stomata. The plant height, number of leaves per plant, and stomatal parameters of the mutant were similar to the wild-type. RNA-seq was used to comprehend the expression variations of waxy cuticle-related genes in the glossy mutant and its wild-type waxy cultivars. Differential gene expression analysis of the RNA-seq data revealed that the genes involved in wax biosynthesis, such as AcCER1, AcCER26, AcMAH1, and AcWSD1, were downregulated by 2.72, 1.74, 2.59 and 2.12-fold, respectively, in the glossy mutant respectively. The expression patterns of these four unigenes were validated using semi-quantitative RT-PCR. The glossy mutant displayed a substantial 3.5-fold reduction in cuticular wax load compared to the wild-type due to the significant downregulation of these wax biosynthesis genes. These findings represent early advancements in understanding the molecular mechanisms of wax biosynthesis in onions. Furthermore, they provide a foundation for utilizing the glossy mutant trait in breeding programmes to enhance stress and pest resilience.